(untitled) (Reflection and Critique Law Magazine, 2023)
This article aims to demonstrate the inefficiency of Law 10,826/03 in containing the crime wave that is increasing on national territory . The following problem was investigated: Has the Disarmament Statute been effective as an instrument to reduce crime in Brazil? The hypothesis that the disarmament law failed to achieve its main objective of reducing crime was considered. Therefore, an analysis of the reasons that culminated in the edition of this law was carried out, as well as a historical analysis of civil disarmament in Brazil and in the world. There was also an analysis of the right to public safety in the face of the right to self-defense. In the body of the work it was presented because the dichotomy existing between the Statute of Disarmament and the guarantees and fundamental rights. Because of the state’s failure to guarantee public safety, the disarmament law only disarmed civilians, while criminals continued to acquire their weapons without any state registration or control in the illegal market. Consequently, it was possible to see that the restrictions imposed by the Statute did not provide for social security, since restricting the legal movement of weapons left the citizen at the mercy of crime.